Analisis Efektivitas Pengendalian Internal Pembayaran Utang Supplier di Hotel Courtyard By Marriott Bali Nusa Dua Resort - Ni Luh Febri Mahendri; I Putu Arnawa; Ni Made Sri Rukmiyati (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the effectiveness of internal control in the supplier debt payment process at Courtyard by Marriott Bali Nusa Dua Resort Hotel. This research uses a qualitative approach with data collection techniques through observation, interviews, and documentation. The analysis was carried out based on the five components of internal control according to the Committee of Sponsoring Organizations (COSO) framework. The results showed that in general, internal control over supplier debt payments at this hotel was in the highly effective category. Of the 15 criteria analyzed based on the five components of internal control, 14 criteria have been met. 1 unmet criterion comes from the risk assessment component, which shows that there are weaknesses in the consistency of implementing debt payment policies to suppliers. The other four components have met all the indicators set, so in general the internal control system can be categorized as very effective. The system implemented has been supported by clear work procedures and information technology in the procurement and debt payment process. However, weaknesses in the risk assessment aspect need to be followed up immediately so as not to have an impact on delays in payments and deteriorating relationships with suppliers.